Gambaran Asupan Energi dan Protein dengan Kejadian Stunting pada Anak Baduta (Bawah Dua Tahun) - Winni Alfioni; Ginta Siahaan (POLTEKKES KEMENKES MEDAN, 2021)
This study aims to determine the description of energy and protein intake with the incidence of stunting in children under two years old (under two years) in the work area of the Mandala Health Center Medan. This type of research is descriptive with a cross sectional design. The results showed that children under the age of five whose energy intake was in the good category experienced stunting by 10%. In conclusion, children under two whose protein intake was in the good category were not found to have stunting. Keywords: Baduta Children, Energy and Protein Intake, Stunting Incident